Analisis Risiko Keselamatan dan Kesehatan Kerja dengan Menggunakan Metode Hazard Identification, Risk Assessment, Determining Control (HIRADC) di Rumah Sakit X Karawang - Alfiansyah, Ridwan; Mukhlisin, Mukhlisin; Rahayu, Siti (LPPM Universitas Pahlawan Tuanku Tambusai, 2025)
This study aims to analyze occupational health and safety (OHS) risks at X Karawang Hospital using the HIRADC method (Hazard Identification, Risk Assessment, and Determining Control). The research focuses on the nutrition installation unit, which has the highest accident rate based on Pareto Diagram analysis. Hazard identification was conducted through observation and interviews with the HSE team, unit heads, and field workers. The results revealed 26 potential hazards, consisting of 2 low risks (7,69%), 20 moderate risks (76,92%), and 4 high risks (15,38%). The main contributing factors include human aspects (lack of OHS awareness), machinery (equipment damage), materials (sharp tools, chemicals), methods (lack of SOPs), and environment (slippery floors, high temperatures). Risk control recommendations include elimination, substitution, engineering controls, administrative controls, and PPE usage. The conclusion emphasizes the need for comprehensive risk control measures to ensure a safe workplace.